STUDI KASUS ANALISIS ASUHAN KEPERAWATAN ANAK DEMAM TIFOID PADA MASALAH KEPERAWATAN HIPERTERMIA DENGAN PEMBERIAN TERAPI KOMPRES TEPID SPONGE DAN TOPIKAL BAWANG MERAH - Yuni, Ni Made Surya Dharma; Prihandhani, IGAA Sherlyna; Yunita Sari, NLP Dian (ASSYIFA : Jurnal Ilmu Kesehatan, 2025)
One of the health challenges often experienced by children is fever, which can be a symptom of various serious diseases such as typhoid fever. Pharmacological management of fever often causes side effects, so safe and effective non-pharmacological alternatives are needed. This study aims to analyze the effectiveness of providing non-pharmacological therapy, namely Tepid Sponge compress and topical shallots as independent nurse actions to overcome hyperthermia in patients. The intervention was carried out on three patients for three consecutive days, with a duration of 35 minutes per session. The results showed a decrease in hyperthermia in all patients, accompanied by increased comfort and ability to do activities. When tepid sponge compress and topical shallots are combined, they work synergistically through two main physiological pathways. external heat release (Heat Loss Mechanism) where tepid sponge compress helps lower temperature through evaporation of water on the skin and shallots accelerate heat release through stimulation of sweat and capillary vasodilation. This combination helps reduce the inflammatory reaction which is the main cause of hyperthermia. The combination of tepid sponge compress and topical red onion works synergistically in lowering body temperature through the mechanism of evaporation, circulation stimulation, and anti-inflammatory effects. This therapy has been proven safe, effective, and potential as an alternative in non-pharmacological pain management with the additional benefit of improving the patient's quality of life. It is hoped that this therapy can be implemented in other pediatric patients.